2011
DOI: 10.1021/es102444g
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated POPs and PAHs in Blood Plasma of Hong Kong Residents

Abstract: The objective of this study was to quantify organic chlorinated pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and polycyclic aromatic hydrocarbons (PAHs) in blood plasma collected from 111 healthy residents in Hong Kong to assess the levels of these pollutants in the general population during the period of March to April, 2008. Concentrations of these residues in blood plasma obtained from the Hong Kong Red Cross Blood Transfusion Service were determined by gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 49 publications
2
32
3
Order By: Relevance
“…Hence, global contamination by DDTs has caused serious concerns about possible adverse health effects to humans and animals (UNEP, 2001). Several previous studies have used DDT and its degradation products in human blood serum as biomarkers for health effects (Laden et al, 1999;Perry et al, 2005;Tiido et al, 2006;Qin et al, 2011), including possible negative effects of DDT on thyroid hormone function during pregnancy (Asawasinsopon et al, 2006;Chevrier et al, 2008;Langer et al, 2009), the effect of serum concentration of POPs in female during gestation (Meeker et al, 2009;Wang et al, 2009) as well as effect to their childhood (Verhulst et al, 2009). Other studies have suggested associations between organochlorine pesticides and type 2 diabetes as well as cardiovascular diseases (Codru et al, 2007;Rignell-Hydbom et al, 2009;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, global contamination by DDTs has caused serious concerns about possible adverse health effects to humans and animals (UNEP, 2001). Several previous studies have used DDT and its degradation products in human blood serum as biomarkers for health effects (Laden et al, 1999;Perry et al, 2005;Tiido et al, 2006;Qin et al, 2011), including possible negative effects of DDT on thyroid hormone function during pregnancy (Asawasinsopon et al, 2006;Chevrier et al, 2008;Langer et al, 2009), the effect of serum concentration of POPs in female during gestation (Meeker et al, 2009;Wang et al, 2009) as well as effect to their childhood (Verhulst et al, 2009). Other studies have suggested associations between organochlorine pesticides and type 2 diabetes as well as cardiovascular diseases (Codru et al, 2007;Rignell-Hydbom et al, 2009;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the findings were perplexing as we detected acenaphthene in only three samples, albeit at high concentrations (> 520 ng/g lipid in three samples) and we cannot exclude analytical uncertainties as the sampling and analyses were not tailored to PAHs in blood. In comparison, a study in Hong Kong reported a median concentration of acenaphthene of 50.3 ng/g lipid and 67.3 ng/g lipid in adult men and women, respectively (Qin et al 2011). Furthermore, we did not find any other PAHs (common co-exposures such as acenaphthylene) in our samples, which could suggest that acenaphthene exposure is inequitably distributed, and perhaps attributable to specific locations within Dhaka or individual behaviors rather than a ubiquitous exposure (e.g., air pollution).…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, significantly higher PBDE levels in human serum from Haojiang than those from Guangzhou (Bi et al, 2006) may point to the consequence of atmospheric transport of PBDEs from Guiyu to adjacent areas. In terms of gender difference, Qin et al (2011b) found that female blood samples contained significantly higher concentrations of p,p′-DDE (942± 224 ng/g lw, p b 0.05) and p,p′-DDT (71.9± 43.9 ng/g lw, p b 0.05) than male samples (756± 312 and 55.2 ±46.7 ng/g lw, respectively) from Hong Kong. By contrast, they obtained comparable levels (mean/median: 5.92/6.77 and 5.25/6.76 ng/g lw, respectively) of PBDEs (sum of between female and male blood samples (p >0.05).…”
Section: Concentrations (Ng/g)mentioning
confidence: 97%
“…A large number of studies have been conducted in the PRD on loadings of POPs in human tissues, including human milk, blood, and adipose tissues (Ip, 1983;Ip and Phillips, 1989;Wong et al, 2002Wong et al, , 2005Poon et al, 2005;Bi et al, 2006Bi et al, , 2007Qu et al, 2007Qu et al, , 2010Qin et al, 2011b). Mean levels of DDTs and HCHs in human milk, collected in 1976, 1985from Hong Kong, decreased from 18.9 and 18.5 μg/g lw in 1976(Ip, 1983 to 13.8 and 16.5 μg/g lw in 1985 (Ip and Phillips, 1989), and further to 2.87 and 0.95 (predominated by β-HCH) μg/g lw in 1999 (Wong et al, 2002).…”
Section: Human Body Burdens Of Popsmentioning
confidence: 99%